Fighting for My Life : How to Thrive in the Shadow of Alzheimer's - Tyrone, Jamie TenNapel; Sabbagh, Marwan Noel; Hanc, John (Nashville, Tennessee : W Publishing, an imprint of Thomas Nelson, 2019)
"A uniquely hopeful exploration of the impact of Alzheimer's disease. This book combines the compelling story of Jamie Tyrone, a self-proclaimed "lab rat" diagnosed with a 91 percent chance of contracting AD, with the medical expertise of Dr. Marwan Sabbagh, a leading authority on Alzheimer's and dementia." --
A question of balance -- The devastating news -- Adventures of a lab rat -- The ABCs of ALZ -- The genetic puzzle of AD -- To test or not to test -- Don't forget the other tests -- The real risks of Alzheimer's -- Out of the mouths of B.A.B.E.S. -- Becoming a caregiver -- Protecting yourself against AD. Part 1, Diet -- Protecting yourself against AD. Part 2, Physical activity -- A world without Alzheimer's? Yes! -- Hear me roar.
Includes bibliographical references.
Keywords: Tyrone, Jame TenNapel -- Health; Biography -- Patients -- United States; Case studies -- Treatment; Treatment; Alzheimer's disease -- Popular works; Mental disorders